(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
In the article revealed the main approaches of scientists, politicians and practitioners to the "cultural and creative industries" category, the state of development of this term in national and foreign literary sources is shown, the genesis of creative industry formation has been demonstrated. As the integral component of the transformation of the industrial system in its postindustrial type proposed methodological tools for the study of the problem, as a symbiosis of theoretical, analytical and empirical elements, identified the main Features of the existing models of creative economy, investigated the creative environment of the advanced countries of the world, classified the main types of cultural and creative industries, selected a number of existing concepts on the impact of creative entrepreneurship on Socio-economic growth of the nation and region, the ways and levers of systematic implementation of a creative approach based on creative thinking human resource, innovation, cultural heritage and financing are suggested. Based on critical thinking, available content, assignments, tasks, directions, methods and tools to uncover a dualistic essence and meaning of the concept of "cultural and creative industries" as a business environment and an object of state economic regulation, as well as to analyze the potential of cultural and creative industries in Ukraine. The goal stipulated the need to solve such problems: to describe the state of development of scientific and practical approaches to the functioning of cultural and creative industries; Indicate the instruments for implementing the creative development strategy; To analyze the experience of European countries on development of creative industry; To analyze and develop perspectives of development of cultural industries in conditions of socio-economic growth of region. A methodological base of the study is the combination of theoretical, applied aspects of the role and significance of creative and cultural industries in the economic and social development of the western region. As well as the system of complementary general scientific, theoretical and experimental methods, in particular: empirical (observation, comparison, generalization), theoretical (dialectical, argumentation), methods used for empirical and Theoretical levels of research (analysis, synthesis, induction, deduction) and others.